A high‐throughput approach to developing and optimizing mixed‐mode membrane chromatography for protein purification. (23rd November 2022) - McKechnie, William S.; Thom, Volkmar; Kupracz, Lukas; Pollard, Jennifer; Kandula, Sunitha; Welsh, John
Abstract: Membrane chromatography has been established as a viable alternative to packed‐bed column chromatography for the purification of therapeutic proteins. Purification via membrane chromatography offers key advantages, including higher productivity and reduced buffer usage. Unlike column chromatography purification, the utilization of high‐throughput screening in order to reduce development times and material requirements has been a challenge for membrane chromatography. This research focused on the development of a new, high‐throughput screening technique for use in screening membrane chromatography conditions for monoclonal antibody purification. The developed screen utilizes a 96‐well plate format, thereby allowing for the screening of multiple different membrane conditions at once. For this study, four mixed‐mode cation exchange membranes and one cation exchange membrane were evaluated on the plate. The screen is performed in a similar manner to that of a resin slurry plate screen, however, instead of a single loading step, the antibody feed was loaded in 50 mg/ml increments up to a maximum loading of 450 mg/ml. Performing a similar, incremental loading on a resin plate would be impractical, as mixing times are substantially longer due to pore diffusion limitations. However, due to the significantly faster rate of mass transfer for membranes relative to resin, mixing times could be reduced by up to a factor of sixty on the membrane plate. Additional optimization showed that higher hydrophobicity can potentially lead to slower kinetics and mixing times that may need to be adjusted accordingly. The end result is a screen that has been proven to provide results comparable to those obtained on larger‐scale membrane purification runs while also enabling exploration of a much greater operating space and significantly reducing the feed materials required.